Seasonal Variation of Pediatric Dermatoses: A Hospital Based Study in Western Hilly Nepal - Shrestha, Pratistha; Mikrani, Jameel Akhtar (Journal of Lumbini Medical College, 2017)
Introduction: Skin diseases are common in children; however they differ depending in age, region, socioeconomic status and climate. Many studies have been done to study pattern of dermatological disease in pediatric age group but only few studies have been done in its seasonal variation. So we decided to study seasonal variation of pediatric dermatoses. Methods: This was a retrospective study done from hospital records of Lumbini Medical College Teaching Hospital (LMCTH). All children 14 years and below attending the Dermatology out-patient clinic with skin diseases between the period of March 2015 to February 2016 were included. Demographic, clinical and laboratory details were recorded. Data were collected and categorized according to four seasons. Microsoft Excel was used for data entry while all analysis, both descriptive and inferential, was done using SPSS version 22. Results: There were a total of 987 children visiting Dermatology clinic during the study period. Of those, 520 (52.7%) were male and the remaining 467 (47.3%) were female with M:F ratio of 1.1:1. Most of the disorders were seen between 10-14 years of age. Majority of visits were in summer (n=403, 40.8%) followed by spring, autumn and winter. Most common dermatosis seen among children during summer was fungal infection (n=91, 9.2%) and during winter was eczema (n=49, 5%). Conclusion: In the present setting there is seasonal variation of dermatological diseases in pediatric age group. DOI: https://doi.org/10.22502/jlmc.v4i1.75 J. Lumbini. Med. Coll. Vol 4, No 1, Jan-June 2016, Page: 32-34